Imaging Tips to Recognize Primary Breast Angiosarcoma. Issue 1 (19th January 2022) - Costa, Patricia; Ferrão, Anabela; Pires-Gonçalves, Lígia
Teaching Point : Primary breast angiosarcoma should be in the differential of a breast mass with rapid growth. It typically appears intensely vascularized and non-calcified, predominantly hyperechoic, and hyperintense on T2-weighted MRI.